2001
DOI: 10.1097/00000658-200106000-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of Simultaneous Kidney–Pancreas Transplantation With Systemic-Enteric Versus Portal-Enteric Drainage

Abstract: These results suggest that simultaneous kidney and pancreas transplantation with SE or PE drainage can be performed with comparable short-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 28 publications
3
61
0
7
Order By: Relevance
“…The incidence of surgical complications is also similar by type of transplant (SPK compared to solitary pancreas transplantation) [1][2][3] . Leaks from the allograft duodenum have been reported to occur in 5%-20% of bladder-drained and 5%-8% of bowel-drained pancreas transplants [9,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][67][68][69][70][71][72][73]80,[91][92][93][94][95] . Increasing experience with enteric exocrine drainage is likewise associated with a decreased rate of technical complications [9,38,80,[96][97][98][99][100][101][102][103] .…”
Section: El-hennawy H Et Al Exocrine Drainage In Pancreas Transplantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of surgical complications is also similar by type of transplant (SPK compared to solitary pancreas transplantation) [1][2][3] . Leaks from the allograft duodenum have been reported to occur in 5%-20% of bladder-drained and 5%-8% of bowel-drained pancreas transplants [9,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][67][68][69][70][71][72][73]80,[91][92][93][94][95] . Increasing experience with enteric exocrine drainage is likewise associated with a decreased rate of technical complications [9,38,80,[96][97][98][99][100][101][102][103] .…”
Section: El-hennawy H Et Al Exocrine Drainage In Pancreas Transplantsmentioning
confidence: 99%
“…However, in most cases, "portal venous" drainage usually infers that the allograft has a vertical orientation with the body and tail directed towards the pelvis, the head and duodenum directed cephalad, and the recipient SMV as the site for the venous anastomosis [18][19][20][21][22] (Figure 4). The bowel anastomosis is most commonly performed to a bowel loop that is not excluded from the transit of intestinal contents [4,16,17,33,[39][40][41][42][44][45][46][49][50][51][52][53][112][113][114][115][116][117][118][119][120][121] . Alternatively, the allograft duodenum can be connected directly into the native stomach or duodenum, to a diverting Roux limb without or with a venting jejunostomy, or to an omega loop [23][24][25][26][27][28][29][30][31][32]122] (Table 7).…”
Section: Bowel Drainage Of the Pancreatic Ductal Secretions (Portal-ementioning
confidence: 99%
“…Being familiar with multiple surgical techniques of PT is helpful because the optimal technique may need to be individualized based on anatomic issues. Purported benefits of PT with portal venous outflow include technical, metabolic, and immunologic "advantages" [2][3][4][5][6][7][8][9]12]. However, these benefits have not been confirmed by either prospective cohort studies, randomized controlled trials, or large analyses based on registry databases [1,[4][5][6][7][8]12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of portal-enteric drainage has never been fully realized as it currently accounts for only 18% of SKPT and PAK and 10% of PTA transplants [1]. A number of studies have demonstrated no major or consistent differences in outcomes for bladder-drained or enteric-drained PTs with either portal or systemic venous drainage [4][5][6][7][8]. Although nearly all PTs are currently performed with one of the three above techniques, current philosophy dictates that the most appropriate technique to be performed is the one with which the surgical team has the most experience.…”
Section: Introductionmentioning
confidence: 99%
“…Recipients of portally drained pancreas allografts usually have lower circulating insulin levels than those with the systemic drainage 27 but no clear difference in metabolic or clinical outcome. 28 Correction of metabolic deficits-Successful pancreas transplantation results in independence from exogenous insulin, normal blood glucose concentration, normal or nearnormal HbAlc, and prompt correction of ketoacidosis. The response to oral and intravenous glucose challenge and to secretagogues such as arginine are re-established.…”
Section: Metabolic Considerationsmentioning
confidence: 99%